Comparative effects of varenicline or combination nicotine replacement therapy versus patch monotherapy on candidate mediators of early abstinence in a smoking cessation attempt. (1st October 2020) - Kim, Nayoung; McCarthy, Danielle E.; Piper, Megan E.; Baker, Timothy B.
Abstract: Background and aims: The phase‐based model of smoking cessation treatment suggests that treatment needs may vary across phases (e.g. pre‐cessation, cessation). This study tested the comparative effects of varenicline and combination nicotine replacement therapy (C‐NRT) relative to nicotine patch monotherapy on pre‐cessation and cessation phase candidate withdrawal, expectancy and motivation mediators; relations between mediators and abstinence; and indirect effects of enhanced treatments on abstinence via candidate mediators. Design: Secondary mediation analysis of data from the open‐label, randomized Wisconsin Smokers' Health Study 2, a comparative effectiveness trial of varenicline or C‐NRT, versus patch monotherapy, in adults who smoked, recruited via media and community outreach. Setting: Research clinics in Madison and Milwaukee, Wisconsin, USA. Participants: A total of 1051 daily smokers motivated to quit smoking (52.5% female; mean age = 48.1, standard deviation = 11.6). Interventions: Twelve weeks of varenicline ( n = 407) or 12 weeks of combination nicotine patch and nicotine lozenge therapy ( n = 421), both compared with 12 weeks of patch control condition ( n = 230), with individual smoking cessation counseling. Measurements: The primary abstinence outcome was biochemically verified 7‐day point‐prevalence abstinence 4 weeks post‐target quit day (TQD). Candidate mediators (craving, positive smoking expectancies, withdrawal symptoms, and quitting motivation) were assessed via ecological momentary assessment from 1 week prior (pre‐cessation phase) to 4 weeks after (cessation phase) the TQD. Findings: Pre‐cessation and cessation mean levels and slopes of craving [adjusted odds ratio (aOR) = 0.34–0.79], smoking expectancies (aOR = 0.46–0.79) and quitting motivation (aOR = 1.35–7.21) significantly predicted 4‐week post‐TQD abstinence ( P < 0.05). Significant varenicline mediation occurred via greater suppression in pre‐cessation craving [mediated effect (ab) = 0.09, standard error (SE) = 0.03, 95% confidence interval (CI) = 0.04–0.14] and smoking expectancies (ab = 0.06, SE = 0.02, 95% CI = 0.02–0.12). C‐NRT mediation occurred via greater reduction in pre–post‐TQD changes in craving (ab = 0.04, SE = 0.02, 95% CI = 0.01–0.08) and expectancies (ab = 0.03, SE = 0.02, 95% CI = 0.001–0.07), relative to patch monotherapy. Conclusion: Among adult smokers seeking to quit, varenicline seems to work through its effects on suppression of craving and smoking expectancies pre‐cessation while combination nicotine replacement therapy mediation seems to work through cessation‐related reduction in craving and smoking expectancies changes.